Glacier bed surveying with helicopter-borne dual-polarization ground-penetrating radar - Langhammer, Lisbeth; id_orcid:0 000-0003-2168-6737; Rabenstein, Lasse; Schmid, Lino; Bauder, Andreas; Grab, Melchior; id_orcid:0 000-0002-8293-4872; Schaer, Philipp; Maurer, Hansruedi (International Glaciological Society, 2019)
Traditionally, helicopter-borne ground-penetrating radar (GPR) systems are operated with a single pair of bistatic dipole antennas to measure the thickness of glaciers. We demonstrate numerically that the directivity of the radiation pattern of single airborne dipoles do not correspond to an ideal full-space solution if the antennas are employed at typical flight heights. These directionality effects can degrade the quality of the subsurface images significantly, when the GPR antennas are orientated unfavorably. Since an adjustment of the antenna orientation is impractical during flight, we have developed a novel dual-polarization helicopter-borne GPR system consisting of two orthogonal pairs of commercial antennas in broadside configuration. To overcome the image quality deficits of the individual channels, we apply a pseudo-scalar approach in which we combine the data of both polarizations. Results of helicopter-borne GPR surveys on two alpine glaciers in Switzerland reveal more coherent bedrock reflections in the summed data compared with single dipole pair profiles. Generally, the dual-polarization setup is more suitable than a single antenna systems, because it is more versatile and less prone to directional effects caused by the placement of the dipole antennas in relation to undulating subsurface reflectors. ISSN:0022-1430 ISSN:1727-5652